Diabetes mellitus and abdominal aortic aneurysms: A review of the mechanisms underlying the negative relationship. (September 2018) - Dattani, Nikesh; Sayers, Robert D; Bown, Matthew J
Introduction: Diabetes mellitus appears to be negatively associated with abdominal aortic aneurysm; however, the mechanisms underlying this relationship remain poorly understood. The aim of this article is to provide a comprehensive review of the currently understood biological pathways underlying this relationship. Methods: A review of the literature ('diabetes' OR 'hyperglycaemia' AND 'aneurysm') was performed and relevant studies grouped into biological pathways. Results: This review identified a number of biological pathways through which diabetes mellitus may limit the presence, growth and rupture of abdominal aortic aneurysms. These include those influencing extracellular matrix volume, extracellular matrix glycation, the formation of advanced glycation end-products, inflammation, oxidative stress and intraluminal thrombus biology. In addition, there is an increasing evidence to suggest that the medications used to treat diabetes can also limit the development and progression of abdominal aortic aneurysms. Conclusion: The negative association between diabetes and abdominal aortic aneurysm is robust. Future studies should attempt to target the pathways identified in this review to develop novel therapeutic agents aimed at slowing or even halting aneurysm progression.